Flow and non-flow event anisotropies at the SPS - Bielčíková, Jana (Nuclear physics. A, Nuclear and hadronic physics, 2003)
A study of differential elliptic event anisotropies (ν2) of charge particles and high-pT pions in 158 AGeV/c Pb+Au collisions is presented. Results from correlations with respect to the event plane and from two-particle azimuthal correlations are compared. The latter give systematically higher ν2 values at pT >1.2 GeV/c providing possibly an evidence of a non-flow semihard component.